A synonymous variant in GCK gene as a cause of gestational diabetes mellitus - Natalia A. Zubkova (Сахарный диабет, 2019)
The diagnosis of MODY as a subtype of gestational diabetes mellitus (GDM) is important for an adequate management during pregnancy and the postnatal period. The present report describes a case of GDM caused by a synonymous с.666CG р.V222V substitution in the GCK gene. The variant, which was initially ranked as likely benign, was later proven to be pathogenic by in vitro studies. The с.666CG substitution led to the use of a new donor splice site and synthesis of the aberrant mRNA with deletion of 16 base pairs. The case illustrates that additional clinical and experimental data may be required for the correct interpretation of sequence variants pathogenicity.